In-between: Crossing the Thresholds of the Urban Skin - Perugia, Francesca; Mancini, Francesco (Lulu, 2020)
Built form is not the only component in the making of space; it is instead a medium enabling the diachronic dialogue between the space and its users. From this perspective, interstitial spaces and thresholds are of higher significance as they mark and govern the relationship between the social and spatial domain. Liminal spaces produced by thresholds are depended upon the physical, visual and symbolical elements defining the spaces. The journey through these spaces is an individual/collective experience consolidating memories and substantiates our sense of belonging, and ultimately, the identity of places. This essay argues that layering, reformulating, blurring and dissociating elements within the architectural spaces frames and influences how the social experience is constructed. The Museum de La Almoina in Valencia (Spain) is used as a case study to explore the making and use of diachronic thresholds and liminal spaces.